Clostridium diï¬ƒcile Infection (CDI) by Hypervirulent BI/NAP1/027 Strain: a Comprehensive Review of Toxigenicity, Pathogenesis, Risk Factors, and Preventative Measures - Budayanti, Ni Nyoman Sri; Aryana, I Gusti Putu Suka; Wedari, Ni Luh Putu Harta (Indonesian Journal of Tropical and Infectious Disease, 2022)
Clostridium diï¬ƒcile is an anaerobic bacil gram-positive bacteria, able to form spores and toxin, that is transmitted among humans through the fecal–oral route. Clostridium diï¬ƒcile infection (CDI), a typical nosocomial infection has been contributed to a signiï¬ cant proportion of morbidity and mortality among in-patients with a case-fatality rate of 14% within 30 days after diagnosis. Profound culture and toxin examination for C. diï¬ƒcile are still minimal in many hospitals in various Asian countries. Consequently, C. diï¬ƒcile reports in Asia remain rare. Highly virulent form of C. diï¬ƒcile caused greater fatality and epidemics severity. Elderly age, hospitalization, exposure to antibiotics e.g., cephalosporins, ï¬‚uoroquinolones, clindamycin, and penicillin contributed as main risk factors. Hypervirulent strain BI/NAP1/027 demonstrated to carry CdtLoc gene locus encodes CD196 ADP-ribosyltransferase (CDT) or known as binary toxin. Virulence factors are TcdA, TcdB, CDTa CDTb in which hypersporulation and mutation of TcD gene by hypervirulent strain led to toxin hyperexpression. Early cases detection, building management team to evaluate patient positive with all C. diï¬ƒcile toxins, hand hygiene improvement, continuation of contact precautions after diarrhea resolution, audit of infection control, and restriction of antimicrobials should be implemented as preventative measures. Focus measures also should emphasize on development of vaccine of C. diï¬ƒcile to boost immune state of elderly people. This review aims to describe severity of disease caused by hypervirulent BI/NAP1/027 C. diï¬ƒcile strain, its mechanism or pathogenesis, risk factors, current treatment options available, along with proposed preventative measures and infection control.